Shear strengthening of RC short columns with ECC jacket: Cyclic behavior tests. (1st April 2018) - Deng, Mingke; Zhang, Yangxi; Li, Qiqi
Highlights: No bond failure between ECC jacket and core concrete was observed. The shear strength was improved by 38–50% after strengthened. The increase in drift capacity and energy dissipation at the ultimate state were up to 111% and 549% respectively. Abstract: This study aims at developing an easy-to-apply strengthening method for reinforced concrete (RC) short columns by using Engineered cementitious composite (ECC), which is a high-performance composite material with tensile strain-hardening behavior and multiple cracking mechanism in tension. Seven identical RC short columns were prepared, and five of them were strengthened with ECC jackets or ferrocement jacket. The main experimental parameters involve the jacketing schemes and the axial load. The failure modes, hysteresis response, deformation capacity, stiffness degradation and energy dissipation capacity of the specimens were studied by the lateral cyclic loading tests. The tests results show that the ECC jacketed columns failed in ductile modes, and exhibited significant improvement in plastic deformation ability and energy dissipation capacity compared with the control specimens. At the ultimate displacement point, the increase of the drift ratio and cumulative energy dissipation of the ECC jacketed columns were 19–111% and 102–549%, respectively, compared with the corresponding control specimens. Under higher axial loads, the ECC jacketing was still certified to be effectively in enhancing the seismic behavior of the original columns. The shear deformation and the shear strength of the original RC columns were effectively improved by the external ECC jacket, and a prediction method for the shear strength of the ECC jacketed columns was given based on the current Chinese codes.